2017
DOI: 10.7448/ias.20.2.21291
|View full text |Cite
|
Sign up to set email alerts
|

Client uptake of safer conception strategies: implementation outcomes from the Sakh'umndeni Safer Conception Clinic in South Africa

Abstract: Introduction: Implementation of safer conception services for HIV-affected couples within primary healthcare clinics in resource-limited settings remains limited. We review service utilization and safer conception strategy uptake during the first three years of Sakh’umndeni, which is a safer conception clinic in South Africa.Methods: Sakh’umndeni is located at Witkoppen Health and Welfare Centre, a high-volume primary healthcare clinic in northern Johannesburg. Men and women desiring to conceive in less than o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 24 publications
1
45
1
Order By: Relevance
“…The studies in the review identified SCSs available or under investigation in sub-Saharan Africa. ART uptake in HIV-infected partners to achieve viral suppression [1113, 1922] and counseling around timed unprotected intercourse (TUI) [23–28] were generally available. Voluntary male medical circumcision for HIV-uninfected men (VMMC) was also discussed as a generally available method of safer conception [11, 14].…”
Section: Resultsmentioning
confidence: 99%
“…The studies in the review identified SCSs available or under investigation in sub-Saharan Africa. ART uptake in HIV-infected partners to achieve viral suppression [1113, 1922] and counseling around timed unprotected intercourse (TUI) [23–28] were generally available. Voluntary male medical circumcision for HIV-uninfected men (VMMC) was also discussed as a generally available method of safer conception [11, 14].…”
Section: Resultsmentioning
confidence: 99%
“…Safer conception strategies, including antiretroviral therapy (ART) use by the HIV-infected partner, preexposure prophylaxis (PrEP) by the HIV-uninfected partner, condomless sex restricted to days with peak fertility, testing and treatment for genital tract infections, voluntary medical male circumcision, vaginal self-insemination, and assisted reproductive interventions (e.g., sperm washing) can minimize HIV risk for serodiscordant couples while supporting pregnancy desires (7)(8)(9)(10)(11). These options vary in cost and acceptability, and timed condomless sex, ART, and PrEP are the most commonly reported strategies used by serodiscordant couples in Africa (8,12,13). However, couples often describe difficulty determining ovulation timing, tracking fertility indicators (e.g., basal body temperature, cervical mucus characteristics), and sustaining timed condomless sex, ART, and PrEP use while attempting pregnancy (12,14,15).…”
Section: Introductionmentioning
confidence: 99%
“…However, couples often describe difficulty determining ovulation timing, tracking fertility indicators (e.g., basal body temperature, cervical mucus characteristics), and sustaining timed condomless sex, ART, and PrEP use while attempting pregnancy (12,14,15). Moreover, research has shown that couples face stigma and healthcare provider bias when seeking safer conception counseling and providers may need additional tools to foster a supportive atmosphere while accurately communicating with a couple about their individual HIV transmission risk (13,14,16,17).…”
Section: Introductionmentioning
confidence: 99%
“…4 While public health efforts to eliminate mother-to-child transmission have made great progress, attention only recently focused on prevention of horizontal transmission among serodiscordant couples trying to conceive. [5][6][7][8] Reduced fertility may alter horizontal transmission risks and is influenced by behavioral, environmental and biological factors. One of the strongest determinants is age, with an inverse relationship with fecundity in women, and to a lesser extent for men.…”
Section: Introductionmentioning
confidence: 99%